Evolution of the skull shape in extinct and extant turtles - Souza, Guilherme Hermanson (2021)
The interplay between form and function (ecomorphology) is a long-standing topic of interest concerning the evolution of the vertebrate skull, with shape being proposed to correlate with factors such as habitat or diet for several groups. Here, I test the hypothesis that different ecological aspects of turtle\'s natural history correlate to their skull shape and use the results of extant taxa to predict the presence of such aspects in their extinct relatives. To accomplish this, I employed geometric morphometrics and multivariate phylogenetic methods to a dataset comprising 93 three-dimensional models of turtle skulls obtained with computed tomography. I found evidence that the skull morphology of extant turtles is structured by allometry, neck retraction, marine habits, and a set of dietary traits including suction-feeding, herbivory and durophagy. When used to infer ecological traits in extinct species, some predictions corroborated previous literature assumptions, such as durophagy in the stem-turtle Eubaena, and marine habits in stemcheloniids. I showed that members of extinct marine groups convergently acquired ecological traits that are similar to those of some extant sea turtles. These include the absence of neck retraction, the presence of herbivory in some extinct nearshore pelomedusoids, and suction-feeding similar to the extant leatherback turtle Dermochelys coriacea among bothremydids, angolachelonians, and likely also in the protostegid Desmatochelys. Overall, my results show an association of multiple ecological factors act in parallel to shape the turtle skull and provide further evidence for the influence of neck retraction capability on it. In addition, I infer previously non-hypothesised features for extinct marine clades, illustrating remarkable instances of convergence during adaptation to marine ecosystems throughout the evolutionary history of turtles.